Assessing the effects of GDP expansion on environmental degradation in uzbekistan - Muhammad Eid Balbaa (GREEN ECONOMY AND DEVELOPMENT, 2024)
This article explores the impact of GDP expansion on environmental degradation in Uzbekistan. Using data from national and international sources, the study examines the relationship between economic growth and key environmental indicators such as carbon emissions, water usage, and land degradation. The findings reveal a strong correlation between GDP growth and increased environmental pressure, highlighting the need for sustainable policies to balance economic progress with environmental protection. Statistical methods, including regression analysis, were applied to ensure robust results and actionable insights.